Harmonising Multiple-Vote Share Structures in the EU: A Visionary Stride or Overreach? - Ihamäki, Eetu (My University, 2024)
The EU public capital markets have experienced a marked decline in IPO activity over recent decades, thus falling behind the leading global markets. In order to make the EU public markets more attractive and facilitate EU companies, particularly small and medium-sized enterprises (SMEs), access to public equity financing, the European Commission introduced the Listing Act initiative in December 2022, featuring a proposal for an EU-wide regulatory framework for multiple-vote share structures (MVSD proposal). The aim of the proposal is to allow multiple-vote share structures in all Member States so that founders and family-owned SMEs can retain control over their businesses while going public. This thesis examines the feasibility and potential implications of harmonising multiple-vote share structures at the EU level. The thesis adopts a doctrinal research method, whilst also incorporating historical and comparative aspects. The doctrinal analysis focuses primarily on the MVSD proposal and its accompanying documents, including the European Commission’s impact assessment, the European Parliament’s proposed amendments, and the opinions of EU stakeholders. Moreover, the analysis is supported by diverse research literature, including both legal and economic studies on multiple-vote share structures. Comparative insights are also drawn from the regulatory approaches of both Member States and non-EU jurisdictions. The thesis’s key finding is that for Member States with strong minority shareholder protection already in place, the MVSD proposal’s de minimis approach achieves an appropriate balance between the interests of controlling shareholders and minority shareholders. However, for Member States with weak minority shareholder protection, further additional safeguards, such as time-based and/or transfer-based sunset clauses, should be considered. In addition, the thesis offers three policy recommendations to enhance the regulatory balance between the interests of minority and controlling shareholders: i) extending the scope of the MVSD proposal to encompass regulated markets; ii) preserving the discretion for Member States or the companies themselves to voluntarily adopt additional safeguards; and iii) requiring companies to disclose information regarding the use of multiple-vote share structures on their official websites.

Listautumiset ovat vähentyneet merkittävästi EU:n julkisilla pääomamarkkinoilla viime vuosikymmenten aikana. Tämän seurauksena EU on jäänyt jälkeen maailman johtavista markkinoista. Lisätäkseen EU:n pääomamarkkinoiden houkuttelevuutta sekä helpottaakseen EU:n yritysten, erityisesti pk-yritysten, mahdollisuuksia kerätä rahoitusta julkisilta markkinoilta, Euroopan komissio julkaisi joulukuussa 2022 Listautumissäädösaloitteen, johon sisältyy ehdotus moniääniosakerakenteita koskevaksi EU:n sääntelykehykseksi (MVSD-ehdotus). MVSD-ehdotuksen tavoitteena on sallia moniääniosakerakenteet kaikissa jäsenvaltioissa, jotta yritysten perustajat ja perheomisteiset pk-yritykset voisivat säilyttää määräysvallan yrityksessään ja samalla listautua julkisille markkinoille. Tutkielmassa tarkastellaankin moniääniosakerakenteiden yhdenmukaistamisen toteutettavuutta ja mahdollisia vaikutuksia EU:n tasolla. Tutkielma hyödyntää lainopillista tutkimusmenetelmää sisällyttäen samalla historiallisia ja vertailevia näkökulmia. Lainopillinen analyysi keskittyy ensisijaisesti MVSD-ehdotukseen sekä siihen liittyviin aineistoihin, kuten Euroopan komission vaikutustenarviointiin, Euroopan parlamentin muutosehdotuksiin ja EU:n sidosryhmien lausuntoihin. Analyysin tukena käytetään lisäksi monipuolista tutkimuskirjallisuutta, joka pitää sisällään sekä oikeudellisia että taloudellisia tutkimuksia moniääniosakerakenteista. Vertailua haetaan myös EU jäsenvaltioiden ja EU:n ulkopuolisten maiden moniääniosakerakenteita koskevasta sääntelystä. Tutkielman keskeisenä havaintona on, että niissä jäsenvaltioissa, joissa vähemmistöosakkeenomistajien suoja on jo entuudestaan vahva, MVSD-ehdotuksen vähimmäisvaatimukset saavuttavat asianmukaisen tasapainon määräysvaltaa käyttävien osakkeenomistajien ja vähemmistöosakkeenomistajien etujen välillä. Vastaavasti, niissä jäsenvaltioissa, joissa vähemmistöosakkeenomistajien suoja on heikko, olisi harkittava lisäsuojatakeiden käyttöönottoa, kuten aikaperusteisia ja/tai siirtoperusteisia raukeamislausekkeita. Tutkielmassa ehdotetaan lisäksi kolmea toimenpidesuositusta määräysvaltaa käyttävien osakkeenomistajien ja vähemmistöosakkeenomistajien etujen välisen sääntelytasapainon parantamiseksi: i) MVSD-ehdotuksen soveltamisalan laajentamista koskemaan säänneltyjä markkinoita; ii) harkintavallan säilyttämistä jäsenvaltioille tai yhtiöille lisäsuojakeinojen käyttöönottamisesta; ja iii) yhtiöiden velvoittamista ilmoittamaan moniääniosakerakenteiden käytöstä verkkosivuillaan.
Keywords: Multiple-vote share structures, Listing Act, SMEs, EU company law, EU securities market law, controlling shareholders, minority shareholders Moniääniosakerakenteet, Listautumissäädös, pk-yritykset, EU:n yhtiöoikeus, EU:n arvopaperimarkkinaoikeus, määräysvaltaosakkeenomistajat, vähemmistöosakkeenomistajat